Pre-operative ondansetron vs. metoclopramide for prevention of post-operative nausea and vomiting in elective lower-segment caesarean section under spinal anaesthesia - J, Vasantha Kumar; P. T., Shivanand; R, Ravi (International Journal of Research in Medical Sciences, 2017)
Background: The problem of nausea and vomiting is a very old but a less thought of problem. Nausea and vomiting are the most common distressing symptom in the postoperative period. Antiemetic drugs play an important role in therapy of post-operative nausea and vomiting (PONV). Though many drugs have been tried as prophylaxis and treatment of PONV, no drug has been proved significantly effective and hence, the present study was undertaken to compare the efficacy and safety of IV metoclopramide and IV Ondansetron as prophylaxis for postoperative nausea and vomiting in lower-segment caesarean section (LSCS) under spinal anaesthesia. Methods: After institutional approval and informed consent 100 ASA I & II patients undergoing non emergent LSCS taken for study. The patients were divided randomly into 2 groups of 50 each. Group I received IV metoclopramide 10mg and Group II received IV. Ondansetron 4mg. Anaesthetic management was standardized. The incidence of vomiting and retching as number of episodes was studied. Nausea was graded depending on the severity and data derived. Results: The mean age, weight and duration of surgery was not significantly different when compared group-1 parturiants with group-2. The mean episodes of emesis, nausea and retching at different postoperative duration were significantly decreased (p<0.05) in Ondansetron group when compared to metoclopramide group as postoperative time progresses. Conclusions: Injection ondansetron 4mg provided decrease in the incidence of PONV than metoclopramide as the side effects with these drugs were minimal.